(3GdefjI hGdCed aj TQM cJGH Gdedd hGdfMds - (3CMeO Hf jMji Hf GdeQJVj GdRjOj,J (B840 (3g` s ((3eMeO Hf EHQGgje GdMLGfi s)
(3ChdgG (B:s
(3Gddge Ef CLd GdKfGA jbUQ Yf hUa LdGdc , hGYXe GdNVhY jbd Yf ELdGdc , hChaQ GdTcQ dGjai HYTjQ eYTGQ EMSGfc s
(3BNQgG (B:s
(3dGjUM Cf jchf eMdkG ddMhGOK ef aQhV GdCYjGf , EP JfRjgg gf GdMjejI dGjJe HOhf Pdc , hGddg CYde hEPG bO aQZfG ef cJGH GdJhMjO heG jJYdb Hg ef GdeSGFd adfTQY ai cJGH GdYOd s
(3GdUaMI GdChdi efgG HNW eZGjQ MOjKs
(3cJHJ GdYfGhjjf HGdMeQIs
(3Ydi MhGTjgG JUMjMGJs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdESdGejs